2013
DOI: 10.1063/1.4821267
|View full text |Cite
|
Sign up to set email alerts
|

Grazing-incidence x-ray fluorescence analysis for non-destructive determination of In and Ga depth profiles in Cu(In,Ga)Se2 absorber films

Abstract: Development of highly efficient thin film solar cells involves band gap engineering by tuning their elemental composition with depth. Here we show that grazing incidence X-ray fluorescence (GIXRF) analysis using monochromatic synchrotron radiation and well-characterized instrumentation is suitable for a non-destructive and reference-free analysis of compositional depth profiles in thin films. Variation of the incidence angle provides quantitative access to the in-depth distribution of the elements, which are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…This analysis technique provides a non-destructive access to compositional depth profiles in thin films (Streeck et al, 2010;Streeck et al, 2013). Applying well-determined synchrotron radiation and calibrated instrumentation allows for a physically traceable quantification based on the knowledge of all relevant experimental and instrumental parameters as well as of the atomic fundamental parameters involved (Hönicke et al 2014), such as photoionization cross-sections, transition probabilities, and fluorescence yields.…”
Section: Reference-free Grazing-incidence X-ray Fluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…This analysis technique provides a non-destructive access to compositional depth profiles in thin films (Streeck et al, 2010;Streeck et al, 2013). Applying well-determined synchrotron radiation and calibrated instrumentation allows for a physically traceable quantification based on the knowledge of all relevant experimental and instrumental parameters as well as of the atomic fundamental parameters involved (Hönicke et al 2014), such as photoionization cross-sections, transition probabilities, and fluorescence yields.…”
Section: Reference-free Grazing-incidence X-ray Fluorescencementioning
confidence: 99%
“…At shallow incidence angles, the fluorescence intensities of the surface-near region dominate, whereas with increasing incidence angle, regions deeper within the Cu(In,Ga)Se 2 layer significantly contribute to the fluorescence intensities detected. For the determination of an elemental concentration distribution (Streeck et al, 2013) from the GIXRF data shown in Fig. 2, a least square method using the Levenberg-Marquardt algorithm (Marquardt, 1963) was employed.…”
Section: Reference-free Grazing-incidence X-ray Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…For the determination of the depth-profile with XPS the XPS acquisition was interspersed with Ar+ ion bombardment and the etch rates were calibrated against the known thin-film stacking sequence obtained using EDX [12]. Among the non-destructive reference-free techniques, Grazing Incidence X-Ray Fluorescence (GIXRF) analysis should be also quoted here; GIXRF has been demonstrated as an appropriate methodology to resolve the In/Ga concentration gradient in the CIGSe thin films utilizing a reference-free approach by using well-known synchrotron radiation and, in particular, radiometrically calibrated instrumentation instead of using reference materials or calibration samples [13,14] The RBS and ERDA techniques belong to the group of Ion Beam Analysis (IBA) techniques that use energetic (MeV) light or heavy ions. The analytical potential and range of applications of IBA techniques in materials science and in particular for thin films analysis has been reviewed by Jeynes et al [15].…”
Section: Introductionmentioning
confidence: 98%
“…Together in the graph the profiles of Se, Ga and Cu are also show determined by the Elemental depth distributions of Cu, Ga, In and Se determined by a fit of GIXRF data measured at the same CIGS absorber bilayers as the a) sample #11 and b) sample #13 are made. For further details of the methodology see the text and[13,26].…”
mentioning
confidence: 99%